The Wits Paediatric Surgical Outcomes Study (WIPSOS): a prospective multicentre observational study in four academic hospitals in Johannesburg - Bhettay, Anisa Zeenat (My University, 2019)
There is limited data on perioperative outcomes in children in South Africa. The South African Paediatric Surgical Outcomes Study, a national multicentre study of perioperative morbidity and mortality in children, reported a postoperative complication rate of 9.7% and an in-hospital mortality rate of 1.1%. The Wits Paediatric Surgical Outcomes Study disaggregated the subset of data in the above study pertaining to the four referral hospitals that comprise the University of the Witwatersrand Academic Hospital Complex to allow meaningful comparison to the national data and other studies. Aim: To describe the incidence of in-hospital perioperative complications including mortality and critical care admission in paediatric surgical patients at the Wits Academic Hospital Complex, and identify associated risk factors. Methods: The Wits Paediatric Surgical Outcomes Study was a prospective observational multicentre cohort study that collected perioperative data for patients < 16 years undergoing non-obstetric surgery during a designated 14-day period. Results: Between 22 May 2017 and 5 June 2017, 399 children received general anaesthesia for a surgical procedure. The median age was 4.42 years and the median American Society of Anaesthesiologists Physical Status 1. The incidence of perioperative respiratory adverse events was 10.3%. The incidence of perioperative cardiovascular adverse events was 4%. The postoperative admission rate to critical care units was 11.5%. Risk factors for adverse events include age under three years and higher ASA PS scores. The all-cause 30-day in-hospital mortality was 1.5%. Conclusions: The paediatric perioperative risk profile differs substantially between high and middle-income countries. While the patient profile seen in this study is similar to the national cohort, the higher complication and mortality rate cannot be accounted for purely by the difference in age and ASA PS, and may be reflective of a healthcare system under stress.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology,Johannesburg, 2019
Keywords: Gastraintestinal System--surgery; Anesthesia--Complications; Anesthesia